Too masculine for healthcare, too feminine for intense sports: correlation between gender conformity and pro-health behaviours - ALEKSANDRA PAWŁOWSKA; KORNELIA LIPOWSKA; DANIEL KROKOSZ (Akademia Wychowania Fizycznego i Sportu w Gdansku, 2021)
Background: The goal of this paper is to examine to what extent levels of femininity and masculinity are associated with practicing several types of health behaviours among individuals who are physically active and inactive. Material/Methods: A total of 559 individuals aged between 35 and 45 (M = 39.4; SD = 3.2) took part in the study. The inactive group consisted of 211 individuals (n = 85 women, n = 126 men), and the active group consisted of 348 individuals (n = 131 women, n = 217 men). The participants completed the following pen-and-paper questionnaires: the Psychological Gender Inventory, the Health Behaviours Inventory, and the Inventory of Physical Activity Objectives. Results: Physical activity and androgynous psychological gender were shown to be associated with the levels of health behaviours in men and women. Among men, femininity turned out to be a factor protective against hegemonic masculinity, while among women it was observed that it is mainly masculinity that correlates with health behaviours. Physical activity was associated with a better psychological attitude. Conclusion: It is possible to treat physical activity as a protective factor against decreased mood and an aid in coping with decreased mood. Society and culture should encourage the development of femininity and masculinity from the earliest years. Future research on masculinity and femininity and pro-health behaviours should be aimed at looking for ways to promote physical activity among undifferentiated individuals.